PEMBELAJARAN DAN BAHAN AJAR MATEMATIKA PADA SEKOLAH MENENGAH PERTAMA DI MALANG DITINJAU DARI TEORI PENDIDIKAN MATEMATIKA REALISTIK - Manopo, Manopo (Widya Warta, 2019)
Instruction conducted by teacher and textbook used by students in school have significant role for success in mathematical learning. Mathematics’ instruction is a learning process built by teacher for developing student’s creativity to improve thinking skill and  the ability to construct a new knowledge as an effort to understand mathematical subject. On the other side, a textbook is a material used to assist teachers on conducting learning process at school.According to PISA’s study, the ability of secondary students in Indonesia in solving mathematical problems which relate to daily life, is still low. This issue may be caused by the instruction and  the textbook in school which do not support the problem solving skill.This research was conducted using observation method on the instruction and the textbook used in eight secondary schools in Malang. The result of observation was compared to Realistic Mathematics Education theory which had five characterictics to supporting student’s skill for solving realistic problems.The result of this research showed the mathematics learning and the textbooks used in the schools did not fit into Realistic Mathematics Education theory yet. The learning in school does not support students’ skill to solve contextual problems and the textbooks used do not supportstudents on practicing in solving problems.